2018
DOI: 10.3390/en11113047
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Hazard of Endogenous Fires in Coal Mines—A Chemometric Approach

Abstract: The most commonly used practice to assess fire hazard development in underground coal mines is based on the measurement of the concentration of selected gases in the mine's air. The main goal of this study was present a strategy to monitor the gaseous atmosphere in the mine in order to identify the onset of an endogenous fire in the coal seam. For that purpose, the principal component analysis (PCA) and the hierarchical clustering analysis (HCA) were applied. The monitoring covers the measurements of concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Energies 2024, 17, x FOR PEER REVIEW 13 of 20 Further improvement of the aerodynamic characteristics of the two-flow air diffuser and the properties of air flow (velocity and temperature fields, velocity and temperature attenuation coefficients, and the influence of the angles of inclination of the twist blades) in terms of aerodynamic resistance and acoustic characteristics of aerodynamic noise, can be achieved as proposed in publication [65]. In order to confirm the effectiveness of the devices implemented to reduce energy consumption, it would be necessary to conduct additional experimental studies applying mathematical models [68][69][70][71] and numerical modelling methods as described in [72][73][74].…”
Section: Modernization Of Building Installationmentioning
confidence: 99%
“…Energies 2024, 17, x FOR PEER REVIEW 13 of 20 Further improvement of the aerodynamic characteristics of the two-flow air diffuser and the properties of air flow (velocity and temperature fields, velocity and temperature attenuation coefficients, and the influence of the angles of inclination of the twist blades) in terms of aerodynamic resistance and acoustic characteristics of aerodynamic noise, can be achieved as proposed in publication [65]. In order to confirm the effectiveness of the devices implemented to reduce energy consumption, it would be necessary to conduct additional experimental studies applying mathematical models [68][69][70][71] and numerical modelling methods as described in [72][73][74].…”
Section: Modernization Of Building Installationmentioning
confidence: 99%
“…The use of non-fl ammable, safe electric infrared heaters in the ground structures of mines and on work areas will minimize the risks associated with increased fi re hazard of the coal industry [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of coal pyrolysis products, thousands of compounds could be observed by GC×GC-TOFMS. Chemometrics, including hierarchical cluster analysis (HCA) and principal component analysis (PCA), , have been employed to determine the relationship between different coals and other various conditions based on the coal properties, proximate and ultimate analyses, trace elements based on ash composition, kinetics of coal pyrolysis, CO, , benzene, cresols, and long-chain aliphatic compounds. Li et al and Yu et al , identified the molecular composition of coal extraction products with FT-ICR MS and Orbitrap MS and obtained in-depth statistical results for seven classes (CH, O, N, S, ON, OS, and NS) by HCA and PCA. However, correlations among the molecular composition of coal pyrolysis products, coal characteristics, and reaction conditions of coal hydropyrolysis have seldom been examined.…”
Section: Introductionmentioning
confidence: 99%